A study of prey-predator model with harvesting on susceptible prey and predator - Verma, Dinesh; Badshah, V.H.; Jain, Suman; Kadam, Nayna (Global Journal of Mathematical Analysis, 2016)
In this paper, we study the prey predator model with susceptible prey and predator. Stability of the system is discussed in the present model. We analyzed the model in terms of catch rate coefficient.